Assessing Political Brand Relationship as Leverage for Voter Preference in Ghana - Glate, Stanley Nelvis (Advances in Social Sciences Research Journal, 2022)
This research is an empirical assessment of political brand relationship as leverage for voter preference and choice of candidates by voters in Ghana. The objective of the study is to ascertain the use of political brand relationships for leveraging the preference of voters. The study used a total sample size of 10 key party and labor union representatives. The research found out that voter identification and differentiation of a political party from one another, as a process, has positive effects on the voting motivations of respondents and their choice of candidates. The research established that the political brand of a party causes voters to accept and identify with a particular party. Finally, the research revealed that the desire to help voters, fulfilment of promises, the creation and sharing of wealth, and safety issues were of paramount concern to voters. The study also found out that, political brand relationship building has a positive impact on voter attraction/preference of the voter. Voters identified themselves with political brands on the basis of brand characteristics such as economic freedom, social status, safety, recognition, and personal achievement. The study further found out that political parties are liable to be neglected by voters when there is a failure to establish a brand relationship. The research recommends that in order to track or monitor changes in aspirations and needs, political parties should undertake regular marketing research with a view to obtaining current information regarding what voters want. The study further recommends that politicians should segment, target, and position their parties or candidates properly in the political market space if they are to be victorious in elections.